Brand Love Mediates Fashion Innovativeness, Perceived Quality, Value for Money, and Word of Mouth Effects - Ida Bagus Putu Wahyadyatmika; Luh Putu Mahyuni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
(1) Fashion innovation continues to develop, so value for money becomes important. Fashion brands that offer high quality products at competitive prices find it easier to attract consumers and win market competition. The revised text is as follows: (2) The formulation of the research problem is to examine whether Fashion Innovativeness, Perceived Quality, Value for Money, and Word of Mouth have an influence on Brand Love and Brand Loyalty, and to analyze whether Brand Love serves as a mediating factor in the relationship between these variables and Brand Loyalty. (3) The purpose of this research is to determine the impact of Fashion Innovativeness, Perceived Quality, Value for Money, and Word of Mouth on Brand Love and Brand Loyalty, as well as to evaluate the mediating role of Brand Love in influencing Brand Loyalty. (4) This research was conducted in the city Denpasar with a total of 150 respondents, data collection was carried out through questionnaires and analyzed using SEM for mediation tests. (5) The research reveals that Fashion Innovativeness and Value for Money have limited impact on Brand Love and Brand Loyalty, with the latter showing a negative effect. Conversely, Perceived Quality significantly influences both Brand Love and Brand Loyalty, while Word of Mouth strengthens Brand Love but does not directly impact Brand Loyalty. Brand Love mediates the effects of Perceived Quality and Word of Mouth on Brand Loyalty, highlighting its importance as an emotional driver of loyalty. These findings suggest that businesses should focus on improving Perceived Quality and fostering positive Word of Mouth to build strong emotional connections with customers, ultimately enhancing Brand Loyalty. Efforts toward Fashion Innovativeness and Value for Money should align with strategies that prioritize customer perceptions of quality and satisfaction.